Peran Otoritas Jasa Keuangan (OJK) Dalam Pengawasan dan Penegakan Hukum di Sektor Perbankan - Muflikh, Alna Aulin Miftakhul; Silalahi, Bob Ben Salomoan; Purba, Calvin Axel; Suwarsit, Suwarsit (Media Hukum Indonesia (MHI), 2024)
This article explores the strategic roles of the Financial Services Authority (OJK) and Bank Indonesia (BI) in supervising and enforcing regulations within the banking sector to ensure the stability of the national financial system. Bank Indonesia, as the central bank, holds primary responsibility for controlling inflation, enhancing production efficiency, and fostering employment growth through well-directed monetary policies. Meanwhile, OJK focuses on integrated oversight across the financial services sector, including banking, capital markets, and non-bank financial institutions, using risk-based and compliance-based supervision approaches. In addressing modern challenges, such as the increasing complexity of banking operations and advancements in financial technology, adaptive regulatory reforms, enhanced supervisory capabilities, and advanced technological tools are essential. Interagency coordination and public participation are critical factors in strengthening oversight, safeguarding the banking sector, and supporting sustainable national economic stability.